"It's always about challenging and supporting": communicative processes of resilience in higher education. Issue 4 (2nd October 2022) - Rossetto, Kelly R.; Martin, Eric M.
ABSTRACT: Based on the vast challenges college students experience, and the current mental health crisis on college campuses, the current study investigated how student-support providers assist and encourage students to enact resilience. We analyzed data from interviews with 25 campus student-support leaders in regard to how they support resilience in college students. Consistent with the communication theory of resilience (Buzzanell, P. M. (2010). Resilience: Talking, resisting, and imagining new normalcies into being. Journal of Communication, 60 (1), 1–14. https://doi.org/10.1111/j.1460-2466.2009.01469.x ), participants discussed interactions and programming that aligned with all five communicative processes (crafting normalcy, affirming identity anchors, maintaining and using social networks, finding alternative logics, legitimizing negative feelings while foregrounding productive action). Further analysis led to four themes, which helped us develop a framework for supporting student resilience that included mattering and belonging, mentorship, reframing and reorientation, and reflection and finding strengths. Using this framework, we discuss theoretical and practical ideas for supporting students through the challenges associated with the college environment.